Numerical Modelling of Rainfall Influence on the Susceptibility of a Slope to Sliding under Induced Compression - Eyo Eyo; Samuel Abbey (Applied Sciences, 2023)
This study examines the pore water pressure responses and stability of an unsaturated–saturated consolidating slope under the influence of rainfall infiltration. Analysis of slope behaviour was carried out with the results obtained for soils having similar saturated coefficients of permeability (ks) of 1 × 10–5 m/s, and rainfall flux (q) of 1 × 10−6 m/s but varying air-entry and coefficient of volumetric compression (mv) values. Results indicate that for the unsaturated portion of the slope (above the groundwater table), negative pore water pressure exists during rainfall infiltration which tends to lessen as the duration of rainfall progresses. An increase in soil compressibility caused a decrease in soil suction in the unsaturated portion irrespective of the rising groundwater level during infiltration. The difference in the pore water distribution was less for mv values below 0.002 kPa−1 especially under major rainfall events. The stability of the slope reduced with an increment in infiltration time as soil compression increased, with the difference being slightly more pronounced under antecedent rainfall of duration greater than 7 days. Although the studied slope appeared to be just safe (factor of safety of 1.2) under the conditions of increased air-entry value, increased compression, and rainfall flux of 1 × 10−6 m/s, the stability of the slope was observed to have been compromised when the rainfall flux was equal to or greater than the saturated coefficient of permeability (1 × 10−5 m/s) of the soil.